2018
DOI: 10.1016/j.apsusc.2018.04.219
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of the photocatalytic activity of magnetic and non-magnetic polymorphs of Fe 2 O 3 in natural sunlight exposure: A comparison of photocatalytic activity

Abstract: The non-magnetic and magnetic polymorphs of iron oxide (Fe 2 O 3 ) namely: α-Fe 2 O 3 (hematite) and γ-Fe 2 O 3 (maghemite) respectively, were synthesized by a facile surfactant aided hydrogel route. The synthesized polymorphs were characterized by diffuse reflectance, photoluminescence and raman spectroscopy for optical properties whereas the morphological, structural, chemical and electronic state evaluation were performed by FESEM, HRTEM, XRD, and XPS. The charge transport and the stability of the materials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…21 The SAED patterns (Figure 1D) showed that four concentric rings corresponded to Fe 2 O 3 (440), Fe (110), Fe 2 O 3 (311), and Fe 2 O 3 (220) crystal planes. 22,23 Therefore, the above results suggested the successful preparation of Fe@Fe 2 O 3 nanowires.…”
Section: ■ Results and Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…21 The SAED patterns (Figure 1D) showed that four concentric rings corresponded to Fe 2 O 3 (440), Fe (110), Fe 2 O 3 (311), and Fe 2 O 3 (220) crystal planes. 22,23 Therefore, the above results suggested the successful preparation of Fe@Fe 2 O 3 nanowires.…”
Section: ■ Results and Discussionmentioning
confidence: 64%
“…In addition, the high-resolution TEM (HRTEM) images (Figure C) showed clear lattice fringes of 2.03 and 2.52 Å, which were the lattice spacings of Fe (110) and Fe 2 O 3 (311) planes, respectively . The SAED patterns (Figure D) showed that four concentric rings corresponded to Fe 2 O 3 (440), Fe (110), Fe 2 O 3 (311), and Fe 2 O 3 (220) crystal planes. , Therefore, the above results suggested the successful preparation of Fe@Fe 2 O 3 nanowires.…”
Section: Resultsmentioning
confidence: 75%
“…Recently, many semiconductors have been under usage as photocatalyst such as TiO 2 , ZnO, WO 3 , MgO, SiO 2 , Fe 2 O 3 , and CdS. [10][11][12][13][14][15][16] Semiconductor photocatalysts have recently demonstrated high photocatalytic activity for decontamination of organic compounds in aqueous solutions. Typically, titania has been revealed as a promising catalyst and has been widely used in photocatalytic degradation of organic contaminants due to its electrochemical properties, low cost, availability, high stability and non-toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…At this point, it is rather unclear if a heterojunction due to slightly varying band positions between the two iron oxide polymorphs within the nanotubes is formed. Heterojunction formation would contribute favorably to charge carrier separation and therefore would be expected to improve photocatalytic activity of the α/γ-Fe 2 O 3 nanotubes as compared to the reference materials (Liu 2012 ; Aslam et al 2018 ).…”
Section: Resultsmentioning
confidence: 99%